ANALISIS EFISIENSI TRAFO FAKULTAS TEKNIK UDAYANA BUKIT JIMBARAN DENGAN PENGOPERASIAN FILTER AKTIF BERBASIS FLC - I N.Triya, Adi Septiawan; Rinas, I W..; Suartika, I.M. (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i02.p30, 2021)
Disruption to the transfomator can result in losses that disrupt the flow of electricity to consumers. Harmonics are disturbances that arise due to the operation of non-linear loads. The purpose of this study is to analyze the efficiency of the KA4214 transformer at the Udayana Bukit Jimbaran Engineering Faculty with harmonics, namely the R = 16.9%, S = 13.8% and, T = 16.1%. . The method used is to simulate and analyze with the results of harmonic measurements in existing conditions, active filters, and active filters based on fuzzy logic controller using Matlab software. The optimal results obtained are using the fuzzy logic controller method with the results of R = 0.85% S = 0.65% T = 0.39% and the efficiency results are 99.99%